Instruments of Property Ownership in Islam: The Study of Inheritance Law - Taqiyuddin, Hafidz; Millah, Mus’idul; Luthfi, Hikmatul (Journal of Islamic Thought and Civilization, 2023)
The current study investigated the role of Islamic inheritance law as a means to ensure the right to property ownership. The "humans and property" theme has garnered widespread interest among scholars and public. Discourse on this topic may be highlighted from economic and legal aspects. Humans, as living beings, cannot be separated from material needs, such as property. In Islam, property is considered one of the trusts granted to human beings as owners in a majāzi sense. Therefore, this study explored the issue of property ownership that originates from inheritance regulated by Islamic law. According to Abu Zahrah, ownership by inheritance is part of special ownership. In order to elaborate this subject, library research method was used along with the analysis of literature based on madhhab doctrines. The study concluded that inheritance is one way of ownership of property through a change of ownership based on ijbāri (God’s provisions). Inheritance is a means of acquiring property, where ownership rights are transferred from a deceased person to his/her living relatives. The transfer of ownership is based on the ijbāri principle (Allah’s decree), rendering inheritance an instrument of property ownership that cannot be endeavored (ikhtiyārī) and determined by human beings. Furthermore, Islamic inheritance law encompasses the principles of bilateral and balanced justice which distinguishes the concept from other legal systems.